PENGEMBANGAN MODUL PEMBELAJARAN FISIKA DENGANPENDEKATAN SAINTIFIK - Yunieka Putri Sukiminiandari; Agus Setyo Budi; Yetti Supriyati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research aims to develop a module to approach scientific measures, which measures the activity is designed to educate participants actively queried mengonstruk concept, law or principle through the stages of 5M covering observe, to question, to reason, to try and form a network. This study uses several stages of research: (1) analysis of needs, (2) Design module (Design module development), (3) Development Tools module, (4) Validation Expert (Content and Media), (5) Revised, (6) Validation Master, (7) Revision, (8) Testing One to One, (9) Revision, (10) of the trial, (11) Revision, and (12) Module Final. Then the module is evaluated by experts of material amounted to 87.33%, results of evaluation of instructional media at 87.71%. High School Physics Teacher evaluation results amounted to 84.20%. The questionnaire results learners small group of 84.69% and the results of the questionnaire participants educate large groups of 84.76%. Based on the results obtained it can be concluded that the media developed a decent used as learning materials physics Keywords: learning media, module, scientific, science process skills.